Strategi Komunikasi Corporate Social and Responsibility PT. Siringo-Ringo Rantauprapat Dalam Pemberdayaan Masyarakat di Sekitar Lingkungan Perusahaan - Lestari, Iko Ayu (Yayasan Haiah Nusratul Islam, Indonesia, 2024)
This research analyzes the Corporate Social Responsibility (CSR) practices at PT. Siringo-Ringo with a focus on community empowerment in the village of Bandar Kumbul. The research method employed is qualitative with a case study approach. The findings indicate that PT. Siringo-Ringo has successfully implemented a holistic CSR program, involving local stakeholders such as village government, community leaders, and the local populace. The CSR program encompasses various areas including education, economics, and community empowerment. This research provides in-depth insights into the positive impacts generated by PT. Siringo-Ringo's CSR program on the company's relationship with the community and local welfare. The implications of these research findings suggest that the qualitative approach offers a profound understanding of CSR dynamics and contributions within the specific context of the company and its local environment.